Kewenangan Negara dan Kewajiban Subyek Hukum Perdata dalam Hubungannya dengan Hukum Pajak - Syukri Hidayatullah (Law Faculty of Universitas Bandar Lampung, 2016)
Although it is understood that the Tax Law is part of the Public Law, but the Tax Law has close links with the Civil Code and mutually concerned. That's because most of the Tax Law looking for basic possibilities for the collection of the events, circumstances and legal acts engaged in environmental civil, such as income, wealth, treaties submission, the transfer of rights as inheritance, compensation, debt relief, and so on. With the enactment of the tax in the form of the Act, means the tax is not a voluntary payment but as an obligation that must be followed so that if people do not meet their obligations will be sanctioned. From the standpoint of the Private Law, the tax in terms of the law is engagement arising from the Law (Tax Law) requires a person who fulfills the conditions prescribed by the Act to pay a sum of money to the treasury state that can be imposed. This research is to discuss the legal relationship between the obligation of natural person as part of Private Law and Tax Law as part of the Public Law.